2021
DOI: 10.1002/cia2.12209
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab in atopic dermatitis patients with chronic hepatitis B

Abstract: The study protocol was approved by the Ethics Review Board of Hyogo College of Medicine and conformed to the ethical guidelines of the Declaration of Helsinki.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Only one case report on two patients with chronic HBV infection in treatment with entecavir and DUP shows no viral reactivation (38) . Furthermore, in a prospective report of five patients treated with DUP who were HBV surface antigen positive and did not receive HBV medication no viral reactivation was detected (39) . TRA phase 3 clinical studies have not reported any cases of HBV reactivation, potentially reflecting trial exclusion criteria for patients with a history of HBV (11) DUP and TRA specifically inhibits Th2 immune responses while having limited effect on Th1 immune responses (40).…”
Section: Hepatitis B Virusmentioning
confidence: 98%
See 1 more Smart Citation
“…Only one case report on two patients with chronic HBV infection in treatment with entecavir and DUP shows no viral reactivation (38) . Furthermore, in a prospective report of five patients treated with DUP who were HBV surface antigen positive and did not receive HBV medication no viral reactivation was detected (39) . TRA phase 3 clinical studies have not reported any cases of HBV reactivation, potentially reflecting trial exclusion criteria for patients with a history of HBV (11) DUP and TRA specifically inhibits Th2 immune responses while having limited effect on Th1 immune responses (40).…”
Section: Hepatitis B Virusmentioning
confidence: 98%
“… 38 Furthermore, in a prospective report of five patients treated with DUP who were HBV surface antigen positive and did not receive HBV medication no viral reactivation was detected. 39 …”
Section: Patients With Past and Current Infectionsmentioning
confidence: 99%
“…Case reports suggest there is no increased risk of hepatitis B reactivation with the use of dupilumab. 81 …”
Section: Hepatitis B and The Use Of Ibsmentioning
confidence: 99%
“…98 Additionally, in a prospective report of five DUP-treated adult patients with AD who were HBV surface antigen positive and did not receive HBV therapy, close monitoring showed no clinically significant elevations in HBV DNA. 99 Since DUP, LEB, and TRA selectively suppress Th2 immune responses 100,101 and HBV suppression occurs through a Th1 response, these biologics are unlikely to cause HBV reactivation. There are no published data for patients with HBV treated with JAKis for AD.…”
Section: Past and Current Infections Of Interestmentioning
confidence: 99%